For single-source feedback, including the mean and percentile rank on feedback by nursing staff does not improve physician-nurse communication amongst anesthesiologists as compared to the raw score alone. (3rd July 2018) - Clarke, Collin; Rostas, Bradley; Nicolauo, George
ABSTRACT: Background: Audit and feedback has increasingly become part of the medical professional landscape as a means to improve quality of practice. While many performance evaluation tools exist, there remains a paucity of research that assesses the relative effectiveness of the various components of assessment and feedback. Using a single-source framework, we investigated the value of a percentile rank score as a feedback tool to promote individual improvement. Method: Ninety peri-operative nurses completed an initial survey assessing the communication skills of 30 anesthesiologists at London Health Sciences Centre using a five-point Likert scale. Physicians were randomized to receive either only their score, or their score compared to the mean along with their percentile rank. An identical survey asking peri-operative nurses to re-evaluate each anesthesiologist's communication skills was sent 3 months later, yielding 76 responses. Results: Regardless of whether or not anesthesiologists received feedback that contained individual scores only or individual scores along with the group mean and percentile rank, there was no significant impact on perceived communication from peri-operative nurses. Conclusions: A percentile rank score was an ineffective component within single-source assessment and feedback to improve peri-operative communication.